Reducing transition costs towards carbon neutrality of China’s coal power plants - Wang, Rui; Cai, Wenjia; Cui, Ryna Yiyun; Huang, Lin; Ma, Weidong; Qi, Binbin; Zhang, Jia; Bian, Jiang; Li, Haoran; Zhang, Shihui; Shen, Jianxiang; Zhang, Xian; et al. (Nature communications, 2025)
The same cumulative carbon emission reduction target can correspond to multiple emission reduction pathways. This study explores how different coal power transition pathways with the same cumulative emissions reductions impact the transition costs, by assessing the dynamic transition processes for coal plants adopting multiple mitigation technologies concurrently or sequentially, such as flexibility operation, biomass and coal co-firing, carbon capture and storage, and compulsory retirement. We develop a plant-level dynamic optimization model and apply it to China’s 4200+ coal plants. We find that under deep decarbonization, the majority of Chinese coal plants retrofit with multiple technologies to reduce emissions and retire naturally at lower costs while contributing to grid stability. Optimizing the pathway can potentially save over 700 billion U.S. Dollars for achieving the same target or increase cumulative emissions reduction from 30% to 50% at no additional cost. This analysis can help inform a cost-effective coal phase-out under China’s carbon neutrality. A well-designed national coal phase-out pathway in China that considers diverse technology portfolios and plant-level sequential decision-making processes can save over 700 billion dollars and elevate mitigation potential.